2022
DOI: 10.1159/000525960
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Horse Allergens Equ c 1 and Equ c 2: A Comparison among Breeds

Abstract: <b><i>Introduction:</i></b> Horse allergens are less studied than allergens from other furry animals and these allergens must be evaluated to understand the complexity of allergy to horses. The aims of this study were to develop assays for the horse allergens Equ c 1 and Equ c 2 in dander and saliva and to determine their levels in ten horse breeds. The study also included a comparison of these findings with previous results on the levels of Equ c 4 performed on the same study populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…The study by Zahradnik et al and the studies by Victor et al [56][57][58] found a high diversity of allergen content in horse hair for Equ c 1 and Equ c 4, as well as in the Curly Horses studied. They did not find a Curly Horse-associated mean lower level of allergens in horse hair or release of allergens during grooming of Curly Horses compared to Quarter Horses.…”
Section: Timementioning
confidence: 87%
“…The study by Zahradnik et al and the studies by Victor et al [56][57][58] found a high diversity of allergen content in horse hair for Equ c 1 and Equ c 4, as well as in the Curly Horses studied. They did not find a Curly Horse-associated mean lower level of allergens in horse hair or release of allergens during grooming of Curly Horses compared to Quarter Horses.…”
Section: Timementioning
confidence: 87%
“…including Curly and Quarter Horses. 15,16 Their results showed high intra-and inter-breed variations as well. No significant differences in allergen contents in horse dander samples between breeds were found.…”
Section: Discussionmentioning
confidence: 98%
“…So far, studies addressing the topic of hypoallergenic breeds have used antibody‐based techniques to quantify allergens in the dust of homes or the animals' coats, saliva, and urine. “Hypoallergenic” dog and horse breeds were not associated with significantly reduced allergen content 14–16,36,37 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations